Guidelines for Constructing Consumption Aggregates for Welfare Analysis - Deaton, Angus (2013)
An analyst using household survey data to construct a welfare metric is often confronted with onfronted with An analyst using household survey data to construct a welfare metric is often confronted with a number of theoretical and practical problems. What components should be included in the overall welfare measure? Should differences in tastes be taken into account when making comparisons across people and households? How best should differences in cost-of-living and household composition be taken into consideration? Starting with a brief review of the theoretical framework underpinning typical welfare analysis undertaken based on household survey data, this paper provides some practical guidelines and advice on how best to tackle such problems. It outlines a three-part procedure for constructing a consumption-based measure of individual welfare: 1) aggregation of different components of household consumption to construct a nominal consumption aggregate; 2) construction of price indices to adjust for differences in prices faced by households; and 3) adjustment of the real consumption aggregate for differneces in household composition. Examples based on survey data fro eight countries--Ghana, Vietnam, Nepal, the Kyrgyz Republic, Ecuador, South Africa, Panama, and Brazil--are used to illustrate the various steps involved in constructing the welfare measure, and the STATA programs used for this purpose are provided in the appendix. The paper also includes examples of some analytic techniques used to examine the robustness of the estimated welfare measure to underlying assumptions.